Boosting University Efficiency via Balanced Scorecard from a Financial and Internal Viewpoints - Abadi, Muhammad Taufiq; Sadali, Ayatullah; Fadzkurrahman A, Muhammad Akbar (International Research Journal of Business Studies, 2024)
This research aims to analyze the performance of the KH Abdurrahman Wahid Pekalongan State Islamic University (UIN) using the Balanced Scorecard (BSC) method which focuses on two perspectives: finance and internal business. The research method used is descriptive with a quantitative approach. Data was collected through surveys, interviews, and analysis of financial documents and internal university performance reports. Financial performance indicators include income, expenses and cost efficiency, while internal business indicators include academic processes, operational efficiency and service quality. The research results show that from a financial perspective, universities experienced a significant increase in annual income, especially from PNBP and academic support. However, there is still a need to diversify income sources. The largest expenditures are allocated to academic activities, staff salaries and allowances, and despite savings efforts, cost efficiency can still be improved. From an internal business perspective, the quality of the academic process is considered good but requires curriculum innovation that is more responsive to job market needs. Campus operational efficiency is good, but several administrative processes require digitalization. The level of student and staff satisfaction with university services is quite high, although there are areas that need improvement such as IT services and supporting facilities. This research concludes that the performance of UIN KH Abdurrahman Wahid Pekalongan from a financial and internal business perspective is quite good, but there are areas that require improvement to achieve higher efficiency and effectiveness. Key recommendations include diversifying revenue sources, increasing expenditure efficiency, curriculum innovation, and digitizing administrative processes.